Preparation method of anti-wrinkle comfortable fabric
By preparing quaternary ammonium modified polysiloxane under a nitrogen atmosphere and emulsifying and finishing treatment, the problem of difficult to improve the wrinkle and antibacterial properties of cotton fabrics in the prior art is solved, and efficient wrinkle and antibacterial effects are achieved. At the same time, the soft and comfortable performance of the fabrics has also been improved.
Patent Information
- Application Number
- CN202411541717.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The prior art is difficult to achieve both the improvement of anti-wrinkle and anti-bacterial properties in cotton fabrics.
By reacting specific chemical substances under a nitrogen atmosphere, quaternary ammonium modified polysiloxane is prepared and emulsified into a finishing solution. The pure cotton fabric is processed through a two-thimmersion and two-roll finishing process to obtain a fabric with anti-wrinkle comfort and antibacterial properties.
The wrinkle and antibacterial properties of pure cotton fabrics have been improved, and the fabric has good soft and comfortable properties while having high wrinkle recovery angle and high antibacterial rate.
Smart Images

Figure CN119553505A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabrics, in particular to a method for preparing wrinkle-resistant and comfortable fabrics. Background Art
[0002] Cotton fiber is a natural cellulose fiber with good air permeability, moisture permeability and comfort properties. The cotton fabric made from it has the advantages of being soft to the touch, comfortable and breathable to wear, and is therefore loved by consumers. However, it is easy to wrinkle and deform after washing, so pure cotton fabrics need to be anti-wrinkle finished.
[0003] For example, the patent with authorization announcement number CN 107558199 B discloses an anti-wrinkle finishing agent for cotton fabrics. The invention uses malic acid, maleic acid, softener, etc. as raw materials to prepare an anti-wrinkle finishing agent for cotton fabrics. After the cotton fabrics are finished with the anti-wrinkle finishing agent, they have the advantages of good anti-wrinkle effect, no formaldehyde release, and not easy to fade, but their antibacterial properties are not improved.
[0004] For example, the patent with authorization announcement number CN 107287899 B discloses an antibacterial finishing method for cotton fabrics. The invention mixes a nano zinc oxide complex solution with a quaternary ammonium salt polymer solution to obtain a zinc oxide-quaternary ammonium salt polymer composite antibacterial agent, which is then configured into an antibacterial finishing liquid. The finishing liquid is used to perform padding treatment on cotton fabrics. The treated cotton fabrics have good antibacterial effects, but do not improve the anti-wrinkle performance of the cotton fabrics. Summary of the invention
[0005] 1. Technical issues to be solved
[0006] In view of the deficiencies in the prior art, the present invention provides a method for preparing an anti-wrinkle and comfortable fabric. The prepared fabric has good anti-wrinkle and comfortable properties as well as antibacterial properties.
[0007] (II) Technical solution
[0008] A method for preparing a wrinkle-resistant and comfortable fabric, the preparation method being as follows:
[0009] (1) Under a nitrogen atmosphere, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, methyltriethoxysilane, aminopropyltriethoxysilane, and polycarboxyl disilane gemini quaternary ammonium salt are added to a flask, stirred and dispersed, reacted at 100-110° C. for 2-4 hours, and then heated to 130-140° C. for 1-2 hours. After the reaction is completed, the mixture is cooled to room temperature, distilled under reduced pressure, and dried to obtain a quaternary ammonium salt-modified polysiloxane;
[0010] (2) mixing the quaternary ammonium salt-modified polysiloxane and the emulsifier uniformly, adding the mixture into deionized water to emulsify the mixture to a solid content of 30%, adjusting the pH to 6-7 with acetic acid, and stirring the mixture to obtain a quaternary ammonium salt-modified polysiloxane emulsion;
[0011] (3) At room temperature, a quaternary ammonium salt-modified polysiloxane emulsion is added to deionized water, stirred and dispersed to prepare a finishing solution, the concentration of which is controlled to be 20-30 g / L, and then pure cotton fabric is added thereto, and a cloth rolling car is used for double dipping and double rolling finishing, the rolling residue rate is controlled to be 80-100%, and the fabric is pre-baked at 100° C. for 5 min, baked at 150° C. for 1-3 min, and placed at 20° C. and a relative humidity of 65% for 24 h to obtain a wrinkle-resistant and comfortable fabric.
[0012] Preferably, in (1), the mass ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, methyltriethoxysilane, aminopropyltriethoxysilane and polycarboxyl disilane gemini quaternary ammonium salt is 100:0.05-0.2:50-100:10-20:10-50.
[0013] Preferably, in (2), the mass ratio of the quaternary ammonium salt modified polysiloxane to the emulsifier is 100:40-60.
[0014] Preferably, in (2), the emulsifier is one of fatty alcohol polyoxyethylene ether 1350 and fatty alcohol polyoxyethylene ether 1390.
[0015] Preferably, in (1), the preparation method of the polycarboxyl disilane gemini quaternary ammonium salt is:
[0016] S1. Under a nitrogen atmosphere, alkyl diamine and acrylonitrile were added to a methanol solvent, and the mixture was stirred at room temperature for 36-48 hours. After the reaction was completed, the mixture was distilled under reduced pressure to obtain an intermediate 1.
[0017] S2. Under a nitrogen atmosphere, add intermediate 1 to a 50% by mass aqueous sulfuric acid solution, stir and disperse, heat to 110-120°C, and keep warm for 3-6 hours. After the reaction is completed, cool to room temperature, filter, wash with deionized water, and dry to obtain intermediate 2;
[0018] S3. Under a nitrogen atmosphere, add intermediate 2, γ-chloropropylmethyldimethoxysilane and sodium iodide to ethanol solvent, stir and disperse, react at 75-85°C for 24-36 hours. After the reaction is completed, cool to room temperature, filter, distill under reduced pressure, and dry to obtain polycarboxyl disilane gemini quaternary ammonium salt.
[0019] Preferably, in S1, the molar ratio of alkyl diamine to acrylonitrile is 1:4-6.
[0020] Preferably, in S1, the structural formula of the alkyl diamine is NH2-R-NH2, R=C n H 2n , 2≤n≤6.
[0021] Preferably, in S3, the molar ratio of intermediate 2, γ-chloropropylmethyldimethoxysilane and sodium iodide is 1:2-2.4:0.02-0.03.
[0022] (III) Beneficial technical effects
[0023] The invention uses alkyl diamine and acrylonitrile as raw materials, and obtains intermediate 1 through addition reaction, and uses cyano group contained therein to hydrolyze in sulfuric acid aqueous solution to obtain intermediate 2, and under the catalysis of sodium iodide, intermediate 2 and gamma-chloropropylmethyldimethoxysilane are subjected to quaternization reaction to obtain polycarboxyl disilane gemini quaternary ammonium salt. Using octamethylcyclotetrasiloxane, polycarboxyl disilane gemini quaternary ammonium salt and the like as raw materials, base-catalyzed copolymerization is performed to obtain quaternary ammonium salt modified polysiloxane, which is then emulsified and configured into finishing liquid, in which pure cotton fabric is immersed, and the anti-wrinkle comfortable fabric is obtained through double dipping and double rolling finishing.
[0024] The finishing liquid prepared by the present invention contains polar groups such as amino and carboxyl groups. After the pure cotton fabric is finished, not only can the moisture absorption performance of the pure cotton fabric be improved, but also the polar groups can be directional adsorbed with the hydroxyl groups on the cotton fiber to form hydrogen bonds and be fixed inside and on the surface of the fiber, thereby limiting the deformation and movement of the molecular chains of the cotton fiber, thereby achieving the purpose of anti-wrinkle.
[0025] The polysiloxane skeleton prepared by the present invention is composed of a Si-O-Si structure, has a large bond angle, a long bond length, and can rotate freely 360 degrees. After the pure cotton fabric is finished, the polysiloxane chain segment can rotate and slide freely on the fiber surface, so that the fabric has good softness and comfort performance.
[0026] In addition, the finishing agent prepared by the present invention contains a quaternary ammonium salt structure with a positive charge, which can be adsorbed to the surface of the cell membrane with a negative charge through electrostatic adsorption, combined with the negatively charged substances on the surface of the cell membrane, destroying the cell membrane, causing the loss of substances in the cell, thereby achieving the purpose of sterilization and antibacterial. The fabric prepared by the present invention has been experimentally confirmed to have good anti-wrinkle and comfort properties and antibacterial properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is the reaction route of polycarboxyl disilane gemini quaternary ammonium salt. DETAILED DESCRIPTION
[0028] "Preferred" in the present invention refers to embodiments of the present invention that can provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0029] Example 1
[0030] (1) Under a nitrogen atmosphere, 0.1 mol of ethylenediamine and 0.4 mol of acrylonitrile were added to a methanol solvent and stirred at room temperature for 48 h. After the reaction was completed, the mixture was distilled under reduced pressure to obtain an intermediate 1.
[0031] (2) Under a nitrogen atmosphere, 0.2 mol of intermediate 1 was added to a 50% by mass aqueous sulfuric acid solution, stirred and dispersed, and the temperature was raised to 115° C. and kept for reaction for 4 h. After the reaction was completed, the temperature was lowered to room temperature, filtered, washed with deionized water, and dried to obtain intermediate 2.
[0032] (3) Under a nitrogen atmosphere, 0.05 mol of intermediate 2, 0.1 mol of γ-chloropropylmethyldimethoxysilane, and 0.001 mol of sodium iodide were added to an ethanol solvent, stirred and dispersed, and reacted at 80° C. for 36 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, vacuum distilled, and dried to obtain a polycarboxyl disilane gemini quaternary ammonium salt.
[0033] (4) Under a nitrogen atmosphere, 20 g of octamethylcyclotetrasiloxane, 0.02 g of tetramethylammonium hydroxide, 10 g of methyltriethoxysilane, 4 g of aminopropyltriethoxysilane, and 2 g of polycarboxyl disilane gemini quaternary ammonium salt were added to a flask, stirred and dispersed, reacted at 105° C. for 4 h, and then heated to 130° C. and reacted for 2 h. After the reaction was completed, the mixture was cooled to room temperature, distilled under reduced pressure, and dried to obtain a quaternary ammonium salt-modified polysiloxane.
[0034] (5) 40 g of quaternary ammonium salt-modified polysiloxane and 24 g of fatty alcohol polyoxyethylene ether 1390 were mixed uniformly, added into deionized water and emulsified to a solid content of 30%, the pH was adjusted to 6 with acetic acid, and stirred to obtain a quaternary ammonium salt-modified polysiloxane emulsion.
[0035] (6) At room temperature, the quaternary ammonium salt modified polysiloxane emulsion is added to deionized water, stirred and dispersed to prepare a finishing liquid, the concentration of which is controlled to be 20 g / L, and then the pure cotton fabric is added thereto, and a cloth rolling car is used for double dipping and double rolling finishing, the rolling residue rate is controlled to be 80%, and the fabric is pre-baked at 100°C for 5 min, baked at 150°C for 3 min, and placed at 20°C and a relative humidity of 65% for 24 h to obtain a wrinkle-resistant and comfortable fabric.
[0036] Example 2
[0037] (1) Under a nitrogen atmosphere, 0.1 mol of 1,3-propylenediamine and 0.6 mol of acrylonitrile were added to a methanol solvent and stirred at room temperature for 42 h. After the reaction was completed, the mixture was distilled under reduced pressure to obtain an intermediate 1.
[0038] (2) Under a nitrogen atmosphere, 0.2 mol of intermediate 1 was added to a 50% by mass aqueous sulfuric acid solution, stirred and dispersed, and the temperature was raised to 115° C. and kept for reaction for 5 h. After the reaction was completed, the temperature was lowered to room temperature, filtered, washed with deionized water, and dried to obtain intermediate 2.
[0039] (3) Under a nitrogen atmosphere, 0.05 mol of intermediate 2, 0.1 mol of γ-chloropropylmethyldimethoxysilane, and 0.0015 mol of sodium iodide were added to an ethanol solvent, stirred and dispersed, and reacted at 80° C. for 30 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, distilled under reduced pressure, and dried to obtain a polycarboxyl disilane gemini quaternary ammonium salt.
[0040] (4) Under a nitrogen atmosphere, 20 g of octamethylcyclotetrasiloxane, 0.01 g of tetramethylammonium hydroxide, 12 g of methyltriethoxysilane, 2 g of aminopropyltriethoxysilane, and 4 g of polycarboxyl disilane gemini quaternary ammonium salt were added to a flask, stirred and dispersed, reacted at 105° C. for 4 h, and then heated to 135° C. and reacted for 2 h. After the reaction was completed, the mixture was cooled to room temperature, distilled under reduced pressure, and dried to obtain a quaternary ammonium salt-modified polysiloxane.
[0041] (5) 40 g of quaternary ammonium salt-modified polysiloxane and 20 g of fatty alcohol polyoxyethylene ether 1390 were mixed uniformly, added into deionized water and emulsified to a solid content of 30%, the pH was adjusted to 6 with acetic acid, and stirred to obtain a quaternary ammonium salt-modified polysiloxane emulsion.
[0042] (6) At room temperature, quaternary ammonium salt modified polysiloxane emulsion was added to deionized water, stirred and dispersed to prepare a finishing liquid, and the concentration was controlled to be 23 g / L. Pure cotton fabric was then added thereto, and double dipping and double padding finishing was performed using a cloth padding car, and the padding rate was controlled to be 90%. The fabric was pre-baked at 100°C for 5 min, baked at 150°C for 2 min, and placed at 20°C and a relative humidity of 65% for 24 h to obtain a wrinkle-resistant and comfortable fabric.
[0043] Example 3
[0044] (1) Under a nitrogen atmosphere, 0.1 mol of 1,4-butanediamine and 0.5 mol of acrylonitrile were added to a methanol solvent and stirred at room temperature for 36 h. After the reaction was completed, the mixture was distilled under reduced pressure to obtain an intermediate 1.
[0045] (2) Under a nitrogen atmosphere, 0.2 mol of intermediate 1 was added to a 50% by mass aqueous sulfuric acid solution, the mixture was dispersed with stirring, the temperature was raised to 110° C., and the reaction was kept warm for 4 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with deionized water, and dried to obtain intermediate 2.
[0046] (3) Under a nitrogen atmosphere, 0.05 mol of intermediate 2, 0.1 mol of γ-chloropropylmethyldimethoxysilane, and 0.001 mol of sodium iodide were added to an ethanol solvent, stirred and dispersed, and reacted at 75° C. for 36 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, vacuum distilled, and dried to obtain a polycarboxyl disilane gemini quaternary ammonium salt.
[0047] (4) Under a nitrogen atmosphere, 20 g of octamethylcyclotetrasiloxane, 0.01 g of tetramethylammonium hydroxide, 15 g of methyltriethoxysilane, 4 g of aminopropyltriethoxysilane, and 6 g of polycarboxyl disilane gemini quaternary ammonium salt were added to a flask, stirred and dispersed, reacted at 100 ° C for 4 h, and then continued to heat to 140 ° C and reacted for 1 h. After the reaction was completed, it was cooled to room temperature, distilled under reduced pressure, and dried to obtain a quaternary ammonium salt-modified polysiloxane.
[0048] (5) 40 g of quaternary ammonium salt-modified polysiloxane and 16 g of fatty alcohol polyoxyethylene ether 1350 were mixed uniformly, added into deionized water and emulsified to a solid content of 30%, the pH was adjusted to 7 with acetic acid, and stirred to obtain a quaternary ammonium salt-modified polysiloxane emulsion.
[0049] (6) At room temperature, quaternary ammonium salt modified polysiloxane emulsion is added to deionized water, stirred and dispersed to prepare a finishing liquid, and the concentration is controlled to be 25 g / L. Pure cotton fabric is then added thereto, and double dipping and double padding finishing is performed using a cloth padding car, and the padding rate is controlled to be 90%. The fabric is pre-baked at 100°C for 5 min, baked at 150°C for 3 min, and placed at 20°C and a relative humidity of 65% for 24 h to obtain a wrinkle-resistant and comfortable fabric.
[0050] Example 4
[0051] (1) Under a nitrogen atmosphere, 0.1 mol of 1,5-pentanediamine and 0.5 mol of acrylonitrile were added to a methanol solvent and stirred at room temperature for 40 h. After the reaction was completed, the mixture was distilled under reduced pressure to obtain an intermediate 1.
[0052] (2) Under a nitrogen atmosphere, 0.2 mol of intermediate 1 was added to a 50% by mass aqueous sulfuric acid solution, stirred and dispersed, and the temperature was raised to 115° C. and kept for reaction for 6 h. After the reaction was completed, the temperature was lowered to room temperature, filtered, washed with deionized water, and dried to obtain intermediate 2.
[0053] (3) Under a nitrogen atmosphere, 0.05 mol of intermediate 2, 0.12 mol of γ-chloropropylmethyldimethoxysilane, and 0.0015 mol of sodium iodide were added to an ethanol solvent, stirred and dispersed, and reacted at 80° C. for 36 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, vacuum distilled, and dried to obtain a polycarboxyl disilane gemini quaternary ammonium salt.
[0054] (4) Under a nitrogen atmosphere, 20 g of octamethylcyclotetrasiloxane, 0.04 g of tetramethylammonium hydroxide, 18 g of methyltriethoxysilane, 3 g of aminopropyltriethoxysilane, and 8 g of polycarboxyl disilane gemini quaternary ammonium salt were added to a flask, stirred and dispersed, reacted at 110° C. for 2 h, and then heated to 130° C. and reacted for 2 h. After the reaction was completed, the mixture was cooled to room temperature, distilled under reduced pressure, and dried to obtain a quaternary ammonium salt-modified polysiloxane.
[0055] (5) 40 g of quaternary ammonium salt-modified polysiloxane and 20 g of fatty alcohol polyoxyethylene ether 1390 were mixed uniformly, added into deionized water and emulsified to a solid content of 30%, the pH was adjusted to 6 with acetic acid, and stirred to obtain a quaternary ammonium salt-modified polysiloxane emulsion.
[0056] (6) At room temperature, quaternary ammonium salt modified polysiloxane emulsion is added to deionized water, stirred and dispersed to prepare a finishing liquid, and the concentration is controlled to be 28 g / L. Then, pure cotton fabric is added thereto, and double dipping and double padding finishing is performed using a cloth padding car, and the padding rate is controlled to be 100%. The fabric is pre-baked at 100°C for 5 minutes, baked at 150°C for 1 minute, and placed at 20°C and a relative humidity of 65% for 24 hours to obtain a wrinkle-resistant and comfortable fabric.
[0057] Example 5
[0058] (1) Under a nitrogen atmosphere, 0.1 mol of 1,6-hexanediamine and 0.5 mol of acrylonitrile were added to a methanol solvent and stirred at room temperature for 48 h. After the reaction was completed, the mixture was distilled under reduced pressure to obtain an intermediate 1.
[0059] (2) Under a nitrogen atmosphere, 0.2 mol of intermediate 1 was added to a 50% by mass aqueous sulfuric acid solution, stirred and dispersed, and the temperature was raised to 120° C. and kept for reaction for 3 h. After the reaction was completed, the temperature was lowered to room temperature, filtered, washed with deionized water, and dried to obtain intermediate 2.
[0060] (3) Under a nitrogen atmosphere, 0.05 mol of intermediate 2, 0.1 mol of γ-chloropropylmethyldimethoxysilane, and 0.001 mol of sodium iodide were added to an ethanol solvent, stirred and dispersed, and reacted at 85° C. for 24 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, vacuum distilled, and dried to obtain a polycarboxyl disilane gemini quaternary ammonium salt.
[0061] (4) Under a nitrogen atmosphere, 20 g of octamethylcyclotetrasiloxane, 0.01 g of tetramethylammonium hydroxide, 20 g of methyltriethoxysilane, 2 g of aminopropyltriethoxysilane, and 10 g of polycarboxyl disilane gemini quaternary ammonium salt were added to a flask, stirred and dispersed, reacted at 100 ° C. for 3 h, and then continued to heat to 135 ° C. and reacted for 2 h. After the reaction was completed, it was cooled to room temperature, distilled under reduced pressure, and dried to obtain a quaternary ammonium salt-modified polysiloxane.
[0062] (5) 40 g of quaternary ammonium salt-modified polysiloxane and 20 g of fatty alcohol polyoxyethylene ether 1350 were mixed uniformly, added into deionized water and emulsified to a solid content of 30%, the pH was adjusted to 7 with acetic acid, and stirred to obtain a quaternary ammonium salt-modified polysiloxane emulsion.
[0063] (6) At room temperature, quaternary ammonium salt modified polysiloxane emulsion is added to deionized water, stirred and dispersed to prepare a finishing liquid, and the concentration is controlled to be 30 g / L. Then, pure cotton fabric is added thereto, and double dipping and double padding finishing is performed using a cloth padding car, and the padding rate is controlled to be 100%. The fabric is pre-baked at 100°C for 5 min, baked at 150°C for 2 min, and placed at 20°C and a relative humidity of 65% for 24 h to obtain a wrinkle-resistant and comfortable fabric.
[0064] Referring to GB / T3819-1977, a fabric crease recovery tester was used to test the wrinkle resistance of the fabric. The fabric size was 40mm×40mm, with ten warps and ten wefts. The test was performed at 20°C and a relative humidity of 65% after balancing for 4 hours. The wrinkle recovery angle WRA value (warp + weft) was used as an indicator of the fabric wrinkle recovery performance.
[0065] Table 1:
[0066] WRA(°) Example 1 245 Example 2 264 Example 3 272 Example 4 278 Example 5 274 Comparative Example 1 233
[0067] Comparative Example 1 is a pure cotton fabric treated with a commercially available finishing liquid, and the finishing process is the same as that of Example 1.
[0068] The larger the wrinkle recovery angle, the better the wrinkle resistance of the fabric. It can be seen from the table that the wrinkle recovery angle of the embodiment is larger than that of the comparative example 1, and in the embodiment, as the amount of finishing liquid increases, the wrinkle recovery angle increases, and the maximum can reach 278°.
[0069] The fabric feel was tested using a fabric style tester. The fabric was balanced for 24 hours at 20°C and 65% relative humidity. Three circular specimens with a diameter of 10 cm were selected from different positions of the same fabric to test its softness and smoothness. The test results ranged from 0 to 100, and the larger the value of each index, the stronger the characteristic of the sample.
[0070] Table 2:
[0071] Softness Smoothness Example 1 80.26 86.40 Example 2 84.33 89.42 Example 3 86.92 93.28 Example 4 89.64 95.16 Example 5 91.25 95.10 Comparative Example 1 76.75 81.44
[0072] Comparative Example 1 is a pure cotton fabric treated with a commercially available finishing liquid, and the finishing process is the same as that of Example 1.
[0073] It can be seen from the table that the pure cotton fabric prepared by the present invention has good softness and comfort performance.
[0074] With reference to GB / T20944.3-2008, the antibacterial properties of pure cotton fabrics were tested, and the test bacteria were Escherichia coli and Staphylococcus aureus.
[0075] Table 3:
[0076] Antibacterial rate (%) Example 1 94.3 Example 2 98.6 Example 3 99.9 Example 4 99.9 Example 5 99.9
[0077] It can be seen from the table that the fabric prepared by the present invention has a good antibacterial effect, and the highest antibacterial rate can reach 99.9%.
[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a wrinkle-resistant and comfortable fabric, characterized in that: The preparation method is as follows: (1) Under a nitrogen atmosphere, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, methyltriethoxysilane, aminopropyltriethoxysilane, and polycarboxyl disilane gemini quaternary ammonium salt are added to a flask, stirred and dispersed, reacted at 100-110° C. for 2-4 hours, and then heated to 130-140° C. for 1-2 hours. After the reaction is completed, the mixture is cooled to room temperature, distilled under reduced pressure, and dried to obtain a quaternary ammonium salt-modified polysiloxane; (2) mixing the quaternary ammonium salt-modified polysiloxane and the emulsifier uniformly, adding the mixture into deionized water to emulsify the mixture to a solid content of 30%, adjusting the pH to 6-7 with acetic acid, and stirring the mixture to obtain a quaternary ammonium salt-modified polysiloxane emulsion; (3) At room temperature, a quaternary ammonium salt-modified polysiloxane emulsion is added to deionized water, stirred and dispersed to prepare a finishing solution, the concentration of which is controlled to be 20-30 g / L, and then pure cotton fabric is added thereto, and a cloth rolling car is used for double dipping and double rolling finishing, the rolling residue rate is controlled to be 80-100%, and the fabric is pre-baked at 100° C. for 5 min, baked at 150° C. for 1-3 min, and placed at 20° C. and a relative humidity of 65% for 24 h to obtain a wrinkle-resistant and comfortable fabric.
2. The method for preparing the wrinkle-resistant and comfortable fabric according to claim 1, characterized in that: In the above (1), the mass ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, methyltriethoxysilane, aminopropyltriethoxysilane and polycarboxyl disilane gemini quaternary ammonium salt is 100:0.05-0.2:50-100:10-20:10-50.
3. The method for preparing the wrinkle-resistant and comfortable fabric according to claim 1, characterized in that: In the above (2), the mass ratio of quaternary ammonium salt modified polysiloxane to emulsifier is 100:40-60.
4. The method for preparing the wrinkle-resistant and comfortable fabric according to claim 1, characterized in that: In the above (2), the emulsifier is one of fatty alcohol polyoxyethylene ether 1350 and fatty alcohol polyoxyethylene ether 1390.
5. The method for preparing the wrinkle-resistant and comfortable fabric according to claim 1, characterized in that: In the above (1), the preparation method of polycarboxyl disilane gemini quaternary ammonium salt is as follows: S1. Under a nitrogen atmosphere, alkyl diamine and acrylonitrile were added to a methanol solvent, and the mixture was stirred at room temperature for 36-48 hours. After the reaction was completed, the mixture was distilled under reduced pressure to obtain an intermediate 1. S2. Under a nitrogen atmosphere, add intermediate 1 to a 50% by mass aqueous sulfuric acid solution, stir and disperse, heat to 110-120°C, and keep warm for 3-6 hours. After the reaction is completed, cool to room temperature, filter, wash with deionized water, and dry to obtain intermediate 2; S3. Under a nitrogen atmosphere, add intermediate 2, γ-chloropropylmethyldimethoxysilane and sodium iodide to ethanol solvent, stir and disperse, react at 75-85°C for 24-36 hours. After the reaction is completed, cool to room temperature, filter, distill under reduced pressure, and dry to obtain polycarboxyl disilane gemini quaternary ammonium salt.
6. The method for preparing the wrinkle-resistant and comfortable fabric according to claim 5, characterized in that: In the S1, the molar ratio of alkyl diamine to acrylonitrile is 1:4-6.
7. The method for preparing the wrinkle-resistant and comfortable fabric according to claim 5, characterized in that: In S1, the structural formula of the alkyl diamine is NH2-R-NH2, R=C n H 2n , 2≤n≤6.
8. The method for preparing the wrinkle-resistant and comfortable fabric according to claim 5, characterized in that: In S3, the molar ratio of intermediate 2, γ-chloropropylmethyldimethoxysilane and sodium iodide is 1:2-2.4:0.02-0.03.
Citation Information
Patent Citations
Antibacterial finishing methods for cotton fabrics
CN107287899B
A wrinkle-resistant finishing agent for cotton fabrics
CN107558199B
Sol-gel method-based sorting method for quaternary ammonium salt antibiotic textile
CN101545203A
Skin-friendly anti-wrinkle fabric and preparation method thereof
CN117344536A
Antibacterial polyester fiber and synthesis process thereof
CN117966478A
Cited By
Cool antistatic comfortable fabric and preparation method thereof
CN120350555A
Crease-resistant garment material and preparation method thereof
CN120844376A
Anti-wrinkle garment fabric and method of making same
CN120844376B
Cool breathable clothing fabric and preparation method thereof
CN120905950A
Cooling and breathable clothing fabric and preparation method thereof
CN120905950B